2000
DOI: 10.1088/0031-9155/45/3/308
|View full text |Cite
|
Sign up to set email alerts
|

Comparative dosimetry in narrow high-energy photon beams

Abstract: A comparison of the response of different dosimeters in narrow photon beams (phi > or = 4 mm) of 6 and 18 MV bremsstrahlung has been performed. The detectors used were a natural diamond detector, a liquid ionization chamber, a plastic scintillator and two dedicated silicon diodes. The diodes had a very small detection volume and one was a specially designed double diode using two parallel opposed active volumes with compensating interface perturbations. The characteristics of the detectors were investigated bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
152
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(161 citation statements)
references
References 25 publications
4
152
0
5
Order By: Relevance
“…Westermark et al 36 applied cone collimators similar to those used in the Gamma Knife Âź ͑ranging in size from 4 to 18 mm in diameter͒ to a Varian Clinac 2100C and studied the output factors of a 6 MV beam using a plastic scintillation dosimetry system based on BC-400 ͑Saint-Gobain Crystals, Hiram, OH͒, as well as a single diode detector, and a double diode, a diamond detector, and a liquid ionization chamber. At these field sizes, the scintillator was shown to consistently measure output factors that were Ն5% lower than the liquid scintillator and measured lower than the diode detectors at most of the field sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Westermark et al 36 applied cone collimators similar to those used in the Gamma Knife Âź ͑ranging in size from 4 to 18 mm in diameter͒ to a Varian Clinac 2100C and studied the output factors of a 6 MV beam using a plastic scintillation dosimetry system based on BC-400 ͑Saint-Gobain Crystals, Hiram, OH͒, as well as a single diode detector, and a double diode, a diamond detector, and a liquid ionization chamber. At these field sizes, the scintillator was shown to consistently measure output factors that were Ն5% lower than the liquid scintillator and measured lower than the diode detectors at most of the field sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Potential disadvantages of increasing beam energy include larger penumbra and the production of secondary neutrons originating in the head of the linac. These neutrons can contribute to integral dose for energies greater than 10 MV, therefore this study will not escalate beam energy beyond this level 29, 30, 31, 32. This work explores the hypothesis that a more penetrating beam may be useful in achieving target coverage while increasing healthy tissue sparing for certain TMI patients.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the narrow penumbra of low‐energy beams results in tighter dose distributions around a target, minimizing irradiation of nearby OARs, although the regions near beam entry ports receive higher doses. ( 6 ) On the other hand, high‐energy beams have negative aspects such as increasingly diffused beam boundaries due to the long lateral range of secondary electrons ( 7 ) and generation of secondary neutrons. The secondary neutrons are generated from the interactions between photons and treatment head when using 10 MV or higher, due to the photoneutron effect.…”
Section: Introductionmentioning
confidence: 99%